Glaucoma Detection in Myopic Eyes: Structural and Vascular Assessment by Optic Coherence Tomography Methods. Issue 12 (6th December 2022) - Cakir, Ihsan; Altan, Cigdem; Yalcinkaya, Gulay; Yayla, Gizem; Alagoz, Nese; Basgil Pasaoglu, Isil; Yasar, Tekin
Abstract : Précis: Retinal nerve fiber layer (RNFL) thickness is helpful in the diagnosis of glaucoma in myopic eyes but neuroretinal rim (NRR) thickness is the most valuable measure. However, changes in optical coherence tomography angiography (OCT-A) parameters are insufficient for the diagnosis of mild to moderate glaucoma in myopia. Purpose: To detect how a multimodal evaluation, which includes RNFL, NRR thickness, and optic nerve head (ONH) OCT-A, affects glaucoma diagnosis in myopic patients. Materials and Methods: Parameters of healthy myopic and myopic glaucoma eyes with an axial length of ≥24 mm were compared. The ONH structural features and peripapillary RNFL thickness were determined with Cirrus 5000 HD-OCT (Cirrus HD-OCT; Carl Zeiss Meditec, Dublin, CA). The Cirrus 5000 HD-OCT with AngioPlex was utilized to perform OCT-A imaging. The sensitivity and specificity levels were calculated by the best cut-off values with area under curve (AUC). Results: One hundred healthy myopic and 54 myopic glaucoma eyes were evaluated. In all areas, myopic glaucoma patients exhibited lower RNFL and NRR thickness than healthy myopic individuals ( P <0.05), with the exception of nasal quadrant RNFL thickness ( P =0.152). The mean entire and 4 quadrants of global radial peripapillary capillary (RPC)-perfusion and global RPC flux index (FI) were significantly lower in the group of myopic glaucoma patients except for the nasal quadrant mean RPC perfusion ( P =0.224). The average RNFL and NRR thickness had a significant difference in AUC for the diagnosis of glaucoma in myopic individuals ( P =0.001, for each). The average NRR showed excellent diagnostic performance, whereas the average RNFL showed good diagnostic performance. Average RPC perfusion and average RPC FI showed poor diagnostic ability. The average NRR AUC was more significant than average RPC perfusion and average RPC FI AUC ( P <0.001). Conclusions: Although RNFL thickness was helpful to diagnose glaucoma in patients with myopia, the diagnostic power of NRR thickness performed best. OCT-A parameters showed poor diagnostic accuracy for glaucoma and the observed perfusion decrease in myopic glaucoma eyes was not sufficiently discriminative compared with NRR and RNFL thickness measurements.